Expansion of a novel population of NK cells with low ribosome expression in juvenile dermatomyositis - Hilliard, Kinsey A.; Throm, Allison A.; Pingel, Jeanette T.; Saucier, Nermina; Zaher, Hani S.; French, Anthony R. (Frontiers in Immunology, 2022)
Juvenile dermatomyositis (JDM) is a pediatric autoimmune disease associated with characteristic rash and proximal muscle weakness. To gain insight into differential lymphocyte gene expression in JDM, peripheral blood mononuclear cells from 4 new-onset JDM patients and 4 healthy controls were sorted into highly enriched lymphocyte populations for RNAseq analysis. NK cells from JDM patients had substantially greater differentially expressed genes (273) than T (57) and B (33) cells. Upregulated genes were associated with the innate immune response and cell cycle, while downregulated genes were associated with decreased ribosomal RNA. Suppressed ribosomal RNA in JDM NK cells was validated by measuring transcription and phosphorylation levels. We confirmed a population of low ribosome expressing NK cells in healthy adults and children. This population of low ribosome NK cells was substantially expanded in 6 treatment-naïve JDM patients and was associated with decreased NK cell degranulation. The enrichment of this NK low ribosome population was completely abrogated in JDM patients with quiescent disease. Together, these data suggest NK cells are highly activated in new-onset JDM patients with an increased population of low ribosome expressing NK cells, which correlates with decreased NK cell function and resolved with control of active disease.